Analyzing Uric Acid Concentration as a Tool to Diagnose Preeclampsia - Faraswati, Riska; Silvia N, Mega (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Preeclampsia is a hypertensive disorder that occurs during pregnancy. So far, uric acid levels have been used as a guide to diagnose preeclampsia. Uric acid is a by-product of metabolism and its levels in the blood can be influenced by various factors, including kidney function and eating habits. This research is an observational study with a prospective approach. In this study, 258 pregnant women were involved at the Wonoasih Community Health Center and Jorongan Community Health Center from March to June 2023. Laboratory examinations were carried out to measure the serum uric acid levels of the research subjects. statistical tests of differences were carried out using SPSS. In pregnant women who suffered from preeclampsia before 34 weeks of gestation and after 37 weeks of gestation with a fetus that was not developing, a significant increase in uric acid levels was found with a Phi coefficient of 0.090 and a contingency test of 0.087. The cut-off point for the uric acid ratio (UAr) test is 1.5, where pregnant women who have been diagnosed with preeclampsia in the 1st trimester of pregnancy have a higher UAr value. The results of the data analysis p value were 0.918 [95% confidence interval (CI): 0.858–0.979) in the group of pregnant women with preeclampsia; This means that uric acid can be a tool for diagnosing preeclampsia in pregnant women